Black adzuki bean (Vigna angularis) extract exerts phenotypic effects on white adipose tissue and reverses liver steatosis in diet‐induced obese mice. Issue 2 (29th September 2016) - Kim, Mina; Pichiah, Pichiah Balasubramanian Tirupathi; Kim, Dae Keun; Cha, Youn‐Soo
Abstract: The primary objective of this study was to examine the extent to which black adzuki bean (BAB) extract attenuates the development of high‐fat diet‐induced obesity in mice. Four‐week‐old C57BL/6J mice were fed one of the following diets for 12 weeks: control diet containing 10% of its energy as fat (CD); high‐fat diet, containing 60% of its energy as fat (HD); high‐fat diet mixed with 1% freeze‐dried BAB extract powder (BAB); or high‐fat diet mixed with 0.08% kaempferol (Kfr). Compared to the HD group, the BAB group showed significantly reduced body weight, reduced white adipose tissue weight, and a reduced adipocyte phenotype. Moreover, the BAB group exhibited decreased signs of liver pathology, decreased liver weight, and decreased formation of hepatic lipid droplets. Lipogenesis‐associated genes were significantly downregulated in epididymal fat tissue, while lipolytic and β‐oxidation genes were upregulated in the BAB group relative to the HD group. Overall, BAB extract is a promising dietary supplement with the potential to attenuate obesity. Practical applications: The adzuki bean has been traditionally consumed as a food and has been used as a traditional remedy in East Asia. Moreover, black adzuki beans have been shown to exhibit beneficial effects, such as anti‐obesity and anti‐steatosis effects, by regulating lipid metabolism.